2019
DOI: 10.1121/1.5119225
|View full text |Cite
|
Sign up to set email alerts
|

Active acoustic cloaking in a convected flow field

Abstract: Acoustic cloaking has mostly been considered within a stationary fluid. The authors herein show that accounting for the effects of convection in the presence of fluid flow is critical for cloaking in the acoustic domain. This work presents active acoustic cloaking in a convected flow field for two different incident fields, corresponding to a plane wave and a single monopole source, impinging on a rigid body. Monopole control sources circumferentially arranged around the rigid body are used to generate a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The derivation of the source coefficient in the form (34) involves expanding the Green's function in the integrand of ( 22) using the first case of the addition formula (26), which holds only for x ∈ R 3 \ D with D defined in (33). From (20), the Kirchhoff-Helmholtz integral equation is identically zero for x ∈ R 3 \ C. For multipolar sources of sufficiently high order, one can thus deduce that u d (x), in the form ( 2) and ( 35), vanishes identically for x ∈ R 3 \(C ∪ D), which is the region exterior to the imaginary spheres centred at the active sources. The radiation-free condition (26) to expand the wavefunctions as one centred at the source at x (the green dot).…”
Section: Supplementary Materialsmentioning
confidence: 96%
See 1 more Smart Citation
“…The derivation of the source coefficient in the form (34) involves expanding the Green's function in the integrand of ( 22) using the first case of the addition formula (26), which holds only for x ∈ R 3 \ D with D defined in (33). From (20), the Kirchhoff-Helmholtz integral equation is identically zero for x ∈ R 3 \ C. For multipolar sources of sufficiently high order, one can thus deduce that u d (x), in the form ( 2) and ( 35), vanishes identically for x ∈ R 3 \(C ∪ D), which is the region exterior to the imaginary spheres centred at the active sources. The radiation-free condition (26) to expand the wavefunctions as one centred at the source at x (the green dot).…”
Section: Supplementary Materialsmentioning
confidence: 96%
“…An illustration of the relation between various methods in acoustics was provided by Cheer [16]. Specific choices of sources can ensure quiet zones and illusions [11,17] and recent work has optimised control sources to reduce the scattered field in passive scenarios and cases with flow for the cloaking of specific objects [18][19][20][21].…”
mentioning
confidence: 99%
“…The current literature has significantly addressed the idea of the active control of Helmholtz scalar fields in broad applications. These include, but are not limited to, active noise control [2][3][4], personal sound zones or multizone sound reproduction [5][6][7], active acoustic cloaking [2,[8][9][10], remote sensing [11,12] and metamaterial design [13][14][15]. Active sound control techniques are becoming increasingly ubiquitous to enhance sound-based systems [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have recently deliberated on the subject. For example, in a series of research papers, Eggler and coworkers theoretically studied active acoustic cloaking for a rigid cylinder in a convected flow field with circumferentially arranged monopole control sources and error sensors 55 , active optimal noise cloaking of rigid and elastic cylindrical shells with circumferentially arranged external monopole control sources or directly applied structural control forces and discrete error sensors 56 , and active optimal acoustic cloaking and illusions of 3D sound-hard bodies (e.g., rigid spheres and cubes) with spherically arranged external discrete monopole control sources and error sensors 57 . It was demonstrated that overlooking the flow effects can cause amplification of the controlled acoustic field due to the constructive interference between the secondary and primary scattered fields.…”
mentioning
confidence: 99%